Pembinaan Masyarakat di Kelurahan Bulutana Kecamatan Tinggimoncong Kabupaten Gowa - Ariesman Ariesman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
Bulutana sub-district is a strategic village in the high muzzle sub-district in terms of religious potential because Bulutana village has 12 customs or what is called the traditional cover of the rua which upholds religious norms, and even has several Islamic education units. The purpose of this Class V STIBA Makassar Real Work Lecture (KKN) is to carry out community service as a pillar of the Tri Dharma of Higher Education. The method of implementing the service program begins with mapping the problems and needs of the community using SOAR Analysis. After the analysis is carried out, the work program is prepared according to the needs of the community. The work programs that were successfully implemented were the Guidance of the Taklim Council, the improvement of reading the Qur'an using the DIROSA method, and the Festival of pious children. The results of KKN activities have an influence and are proven to provide significant changes that are felt by the community regarding their reading of the Qur'an, their interaction with the Qur'an and providing a good understanding of religion as well as increasing the enthusiasm of children and the younger generation to Islam properly by carrying out its values. .